PENGGUNAAN MEDIA SOSIAL DI KALANGAN GEN Z DAN ALPHA - Halwa Hannisa; Vita Amelia; Nining Sudiar (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This study aims to analyze the habits, reasons, and impacts of social media use among generation z and alpha. The method used is descriptive quantitative with data collection techniques in the form of observation, interviews, questionnaires, and documentation. The population of this study amounted to 24,926 people consisting of generation z and alpha in Sidomulyo Barat urban village, with a sample of 394 people selected using certain sampling techniques. The results showed that there were no significant differences in the patterns, reasons, or impacts of social media use between these two generations. The most widely used types of social media are whatsapp, tiktok, and instagram. Most respondents access social media using wifi as the main connection source, and the dominant device used is a smartphone. The average length of social media use is three years, with an average access time of two hours a day. The preferred place to access social media is at home. The main reason for using social media is for entertainment, followed by the need to get information. The perceived positive impacts include the ease of communicating with friends or family, while the most commonly reported negative impacts are causing addiction and spending too much time which can interfere with productivity.